PENGARUH TUNTUTAN KERJA DAN USIA TERHADAP KEPATUHAN KARYAWAN DENGAN REWARD SEBAGAI VARIABEL MEDIASI (STUDI PADA KLINIK X DI KABUPATEN CIREBON) - Fauzan Fauzan; Mira Veranita; Purwadhi Purwadhi (JURNAL EKONOMI BISNIS DAN MANAJEMEN (EKO-BISMA), 2025)
Work demands affect employee compliance in the work environment. The varying age of employees also influence employee compliance in the workplace. The appropriate rewards for employees from management/owners also play a role in employee compliance. With good employee compliance, the company/clinic can meet its business objectives effectively. The aim of this research is to determine and analyze the effect between work demands and age on employee compliance, mediated by rewards as the mediating variable. The research conducted at clinic X in Cirebon Regency with a population of 40 people. The sampling technique used is total sampling with inclusion and exclusion criteria, resulting in a sample size of 28 respondents. This type of research is observational quantitative research. Data analysis using linear regression and mediation testing with prior validity and reliability tests. The results of the study show a significant effect of work demands on employee compliance, however there is no significant effect between work demands and age on employee compliance with reward as a mediating variable.The importance of management implementing communicative and participative leadership, fair and transparent rewards and team based work programs.